Дифракция волн на индуктивных диафрагрмах конечной толщины в прямоугольных волноводах - Кириленко, А.А.; Масалов, С.А.; Шестопалов, В.П. (Radiotekhnika)
Дифракция волн на индуктивных диафрагрмах конечной толщины в прямоугольных волноводах